A STUDY ON PERSONALITY AMONG DIFFERENT ENGLISH PROFICIENCY STUDENTS (A CASE STUDY ON 8th SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF FACULTY OF CULTURAL STUDIES) - KHUSNA, FARIHANUN (Jurnal Ilmiah Mahasiswa FIB, 2013)
Every person has his or her unique personality. Personality is one of factors affecting language learning. There have been some studies analyzing about personality profile towards language proficiency, but no research tries to use the students of English Program as the participant. This research aims to investigate about: (1) the dominant personality profile and (2) differences and similarities on personality profile among 8th semester students of English Study Program, Faculty of Cultural Studies at Brawijaya University in each language proficiency level.This research used questionnaire of Cognitive Style inventory© by Ross Reinhold, INTJ (2006) given to 60 participants. Those participants are divided into 3 groups based on their language proficiency levels. Those group classifications are 20 participants in Beginning level (with TOEFL score less than 450), 20 participants in Intermediate level (with TOEFL score around 450 to 513), and 20 participants in Advanced level (with TOEFL score more than 513).The result of the study indicates that students with different language proficiency levels have different dominant personality profile. Beginning level has Extrovert Sensing Thinking Perceiving and Extrovert Sensing Thinking Judging as the dominant personality profiles. Then Introvert Sensing Thinking Judging becomes the dominant personality profile in Intermediate level. For advanced level, the most dominant is Extrovert Sensing Thinking Perceiving. Besides, differences are found in this research. They are located on the difference dominant of personality profile in each language proficiency types and the different percentage reached by several personality profiles in each language proficiency level. In addition, the similarity is found on Extrovert Sensing Thinking Perceiving being the dominant personality profile in beginning and advanced level. Then the similarity is also indicated on 3 personality profiles getting the lowest percentage in all language proficiency levels.From the result of the research, it is shown that Extrovert Sensing Thinking Perceiving is the dominant personality type in all language proficiency levels. Then this research suggests that the future researcher will be able to make a research with different subject or use different aspect that could be related to personality type. Keywords: Personality, Language proficiency, Language Learning